Development of a protocol for conducting a randomized control trial on effects of artificial intelligence on nutritional status of children post cardiac surgery - Zahid, Maryam; Ume Sughra (Journal of the Pakistan Medical Association, 2022)
Objectives: To assess the effect of diet-related mobile application based on artificial intelligence on the nutritional status of children post-cardiac surgery, and to compare their diet-related problems with their counterparts having the usual diet. Method: The two-arm double-blind randomised controlled trial will be conducted at a tertiary care hospital in Rawalpindi, Pakistan, over an expected duration of 6 months from March to August 2021. Intervention group A will be given a diet-related mobile application based on artificial intelligence, while usual-care group B will be handed a pamphlet with instructions related to post-operative diet on discharge. Results: The findings will improve perception about the influence of artificial intelligence on nutritional status of children post-cardiac surgery. If proven to be effective, this mobile application can be used in other hospitals. Conclusion: The study protocol will give an indication that whether diet-related mobile application can contribute to improving the nutritional status of children post-cardiac surgery. As the pandemic has forced people to minimise hospital visits, this is the right time to evaluate the utility of such an application. Key Words: Artificial intelligence, Diet-related mobile application, Nutritional status, Children post-cardiac surgery, Randomised controlled trial.